Polygenic Risk Scores disclosure for cardiovascular prevention: Protocol of the Personalized HeartCare (PHC) trial - Luigi Russo; Luca Proto; Sara Farina; Eleonora Pascucci; Riccardo Galarducci; Tina Pasciuto; Anna Severino; Giovanna Liuzzo; Andrea Urbani; Ivo Iavicoli; Roberta Pastorino; Stefania Boccia (PLoS ONE, 2026)
Background Cardiovascular diseases (CVDs) are the leading cause of death and morbidity in Europe, highlighting the need for innovative and personalized prevention strategies. Communicating genetic risk through Polygenic Risk Scores (PRSs) may help promote healthier behaviors, though evidence remains limited. This trial aims to assess whether PRS disclosure can support lifestyle changes and its implementation into clinical practice. Methods The PHC study is a single-arm clinical trial whose primary objective is to assess the effectiveness of communicating CVD PRSs in modifying the lifestyle behaviors, based on the Life’s Essential 8 (LE8) questionnaire. Secondary endpoints include changes in SCORE2 and LDL-cholesterol levels. Additionally, the study aims to evaluate the feasibility and acceptability of the intervention for participants and physicians, and the working ability through the Work Ability Index. The trial enrolls 650 healthy participants from the general population, aged over 40 years, who must have a 10-year CVD risk of less than 10% on the SCORE2 charts or less than 15% on the SCORE2-OP. All participants undergo an initial assessment at baseline (T0), a disclosure visit one month later (T1) to receive the PRS and lifestyle results, and health recommendations, and a final follow-up at six months (T2) for the reassessment of lifestyle behaviors and modifications. Discussion This study explores the innovative use of PRS to enhance primary prevention of cardiovascular diseases, potentially improving individual risk stratification beyond traditional clinical models. By combining PRS with conventional factors, it aims to test whether disclosure can motivate lifestyle improvements. Furthermore, it explores the practical integration of PRS communication into routine care, assessing both participant acceptance and clinician workflow impact, offering insights into real-world implementation of PRS. The findings may inform how PRS can be integrated into clinical workflows, contributing to advance personalized prevention strategies, and help implement PRS-based interventions in health systems. Trial registration number ClinicalTrials.gov NCT06888466 .